Antitumor Drug Combretastatin-A4 Phosphate Aggravates the Symptoms of Dextran Sulfate Sodium-Induced Ulcerative Colitis in Mice - Tang, Zhengshan; Xiong, Dehui; Song, Jianhui; Ye, Mao; Liu, Jing; Wang, Zi; Zhang, Lei; Xiao, Xiaojuan (Frontiers in Pharmacology, 2020)
Ulcerative colitis (UC) is an idiopathic inflammatory bowel disease (IBD) that causes long-lasting inflammation and ulcers in the innermost lining of the colon and rectum. Previous studies demonstrated that resveratrol suppresses colitis and colon cancer associated with colitis by improving glucose metabolism, but resveratrol use is limited by its low oral bioavailability. Combretastatin-A4 phosphate (CA4P) is a vascular-disrupting agent with antitumor activity. CA4P is structurally similar to resveratrol, but whether CA4P has the same effect as resveratrol on UC is not clear. In this study, we examined the pharmacological effects of CA4P administration on dextran sulfate sodium (DSS)-induced inflammation in a mouse model of UC. C57BL/6 mice were administered 2.5% DSS in the drinking water to induce acute UC. CA4P (11mg/kg/day) was injected intraperitoneally daily. The disease activity index (DAI) score and histological score were evaluated to determine the severity of ulcerative colitis. Colon tissues and blood samples were collected for histological analyses. The results show that CA4P plus DSS significantly decreased colon length (P<0.05 versus DSS+PBS group) and body weight (P< 0.001 versus PBS group), while increased spleen weight (P< 0.01 versus DSS+PBS group), DAI score (P< 0.01 versus DSS+PBS group) and histological score (P< 0.01 versus DSS+PBS group). Moreover, CA4P exacerbated the pathological features of colitis and significantly increased proinflammatory cytokines (IL-1β, IL-6, TNF-α) and inflammatory cells (neutrophil, lymphocyte, monocyte). These findings reveal that CA4P aggravates the symptoms of DSS-induced UC and provide a key reference for the potential of CA4P as an anticancer drug.